2007
DOI: 10.1536/ihj.48.755
|View full text |Cite
|
Sign up to set email alerts
|

Increased Functional Importance of the Na,Ca-Exchanger in Contracting Failing Human Myocardium but Unchanged Activity in Isolated Vesicles

Abstract: SUMMARYThe present study aimed to investigate the hypothesis that the function of the Na,Caexchanger (NCX) is of higher importance for contractility and Ca 2+-homeostasis in left ventricle from terminally failing than from nonfailing human hearts.The effect of decreasing extracellular [Na] e (140 to 25 mmol/L) on force of contraction in isolated left ventricular papillary muscle strips was studied as a reflection of NCX function in multicellular preparations (terminally failing, DCM, dilated cardiomyopathy, NY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…However, we can begin to speculate that the observed flexibility, alterations of cTnT-FHC mutations, such as R92L (16), may lead to abnormal thin-and thick-filament interactions sufficient to directly impair systolic and diastolic perfor- http://ajpheart.physiology.org/ mance at the whole heart level. R92W pathogenesis, on the other hand, exhibits a temporal disease progression characteristic of a classic heart failure response, with its impairments in SERCA2a-to-PLB ratio and SR Ca 2ϩ uptake and the increased NCX protein levels (9,17,38,43). Nonetheless, the agedependent improvements observed in R92W contractility, Ca 2ϩ kinetics, and Ca 2ϩ homeostasis uncover a novel underlying mechanism via the initial, presumably compensatory actions of PLB phosphorylation and CaMKII-mediated Thr17 phosphorylation in particular.…”
Section: Discussionmentioning
confidence: 99%
“…However, we can begin to speculate that the observed flexibility, alterations of cTnT-FHC mutations, such as R92L (16), may lead to abnormal thin-and thick-filament interactions sufficient to directly impair systolic and diastolic perfor- http://ajpheart.physiology.org/ mance at the whole heart level. R92W pathogenesis, on the other hand, exhibits a temporal disease progression characteristic of a classic heart failure response, with its impairments in SERCA2a-to-PLB ratio and SR Ca 2ϩ uptake and the increased NCX protein levels (9,17,38,43). Nonetheless, the agedependent improvements observed in R92W contractility, Ca 2ϩ kinetics, and Ca 2ϩ homeostasis uncover a novel underlying mechanism via the initial, presumably compensatory actions of PLB phosphorylation and CaMKII-mediated Thr17 phosphorylation in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in the electrochemical gradient of sodium reduce or even revert the NCX function, leading to increased intracellular concentration of calcium and, consequently, increased force. 28,32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Diedrichs et al 33 have shown that the cardiac muscle in patients with heart failure is more sensitive to a reduction in extracellular sodium, exhibiting a greater increase in contractile force when compared with the muscle in normal individuals. According to the authors, this is due to intracellular calcium accumulation via NCX, whose expression and function is increased in heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to animal models, increased NCX mRNA and protein abundances in failing human heart have been reported[162, 169]. The functional role of the NCX in failing human myocardium is of greater importance to Ca 2+ -homeostasis than in non-failing myocardium due to the altered function of SR[170]. However, the alterations of NCX in HF are controversial; unchanged levels of NCX protein in human heart failure have been reported[171, 172], and some have reported a HF-related decrease in NCX expression[173] [174].…”
Section: Heart Failure-related Electrophysiological Remodelingmentioning
confidence: 91%